PEMAKNAAN HAK MENGUASAI NEGARA ATAS TANAH DALAM DIMENSI POLITIK HUKUM KONSTITUSI - Bachtiar Baetal; Dwi Kusumo Wardhani; Dian Ekawati (Universitas Pamulang, 2021)
AbstractConstitutionally, the state no longer acts as the owner of the land, but only as the holder of the right to control. In the principle of state control, the relationship between the state and society, society cannot be subordinated to its position under the state, because the state actually receives power from the community to regulate the allocation, supply and use of land, as well as legal relations and legal actions with land. The authority to regulate by the state is also limited, both by the Constitution and its relevance to the objectives to be achieved. However, at a practical level, there is no common perception regarding the definition of State Controlling Rights over land or state land, so that there is often a bias and disorientation related to land policy itself. Therefore, the meaning of the concept of state control over land must be returned to the meaning desired by the constitution.Keyword: Meaning, the right to control the state over land, Constitution